Hubungan Nilai Viral Load Dengan Jumlah Cd4 Pada Pasien Hiv/Aids Di Laboratorium Nasional De Saude Timor Leste - Silva, Laura Maia Da; Andini , Komang Sukra (CV. Green Publisher Indonesia, 2025)
Human immunodeficiency virus (HIV) is a disease that attacks the human immune system, Claster of Differention cells CD4. HIV Infection can cause by AIDS, which is an advanced disease of HIV. At 2022 cases of HIV in Timor Leste were 2050 people’s. Most of suffers at the productive age at 25-44 years were 59%. The porpose of study is to know corelation of viral load and CD4 cout at patients of HIV/AIDS at Nasional Health Laboratory. Location of study is at National health laboratory. The date has been collected in period of January-March 2024. The method used in this study is a descriptive method with a correlational reseach. The technique sampling used in this study is simple ramdom sampling. Time for study is beginning in February-March 2025 with population 120 people’s and sample was 92. The viral Load result was undetectable at 46 (50,0%), the normal CD4 result at 37 (40,2%)). The result of spearman rank test of P value = 0.001, r = 0,343 means that singnificant value <0.05 then there is a correlation between viral loads and CD4. The Viral Load’s and CD4 are corrolate because the higher of viral load value, and the lower of CD4 count cell. Concluded that there is a significant relationship between viral load and CD4 count.